The impact of employment equity transformation on the performance of air traffic and navigation services (SOC) limited - Musandiwa, Lutendo (My University, 2024)
The purpose of this study was to investigate how the implementation of employment equity transformation has affected the overall performance of Air Traffic and Navigation Services. To achieve the purpose of this study, a quantitative research design was used. Data were obtained from ATNS employees including executive managers, senior managers, junior managers, administrators, and specialists. A structured questionnaire was used to collect data from the participants. The collected data were analysed quantitatively, with the use of SPSS. The findings of the research revealed that ATNS has put in place initiatives that address EE transformation in the organisation, therefore, black people, women, and people with disabilities are proportionally represented at ATNS. Furthermore, ATNS provides those in the EE-designated group, opportunities for training and development, therefore, ATNS is proactive in the elimination of inequality and discrimination in the workplace. The findings showed that, although, there is a commitment at managerial level for EE transformation, however, there are challenges, such as, insufficient consultation and communication on EE transformation issues, within the organisation. The conclusions were that employees are treated in an unbiased manner and that the EE transformation process has had an impact on the attraction and retention of diverse workforce; this in turn has positively impacted the profit and revenue of ATNS. The study recommends that ATNS should encourage transparency on EE transformation issues, to enable open and effective information-sharing in the organisation. This would create awareness, among the public, of how the employment of black people, women and people with disabilities has resulted in an increase in ATNS’ profit and revenue, hence, ATNS should increase disability awareness initiatives in the organisation.
Thesis (MPAM.) -- University of Limpopo, 2024
Keywords: Employment Equity; Designated group; Employment Equity Transformation; Equity; Air traffic control; Employment portfolios; Performance -- Management